The Effect of Nutrition Literacy Intervention on Maternal Behavior in Providing Local Food-Based Complementary Feeding in Children Aged 6-24 Months - Simbolon, Demsa; Yuranti, Faza (Jurnal Kesmas Jambi, 2026)
Proper complementary feeding for children aged 6–24 months is essential to meet nutritional needs beyond breast milk. Maternal nutrition literacy plays an important role in improving knowledge, attitudes, and practices related to providing local complementary feeding. This study aimed to analyze the effect of an “Isi Piringku”-based nutrition literacy intervention delivered through educational flyers on maternal knowledge, attitudes, and practices in providing local food-based complementary feeding for children aged 6–24 months. This study employed a quasi-experimental design with a pretest–posttest control group approach. The research was conducted in the working area of Sawah Lebar Health Center, Bengkulu City, from May to June 2024. A total of 60 mothers with children aged 6–24 months were selected through purposive sampling and divided into an intervention group (n=30), which received educational flyers, and a control group (n=30), which received leaflets. Data on knowledge, attitudes, and practices were collected using structured questionnaires before and after the intervention. Statistical analysis was performed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test at a 0.05 significance level. Results showed significant improvements in knowledge, attitudes, and practices in both groups after the intervention (p<0.05). However, the intervention group demonstrated significantly higher post-test scores compared to the control group across all variables. Educational flyers were more effective in enhancing maternal nutrition literacy and improving local complementary feeding practices and can be recommended as a community-based nutrition education strategy.